Caught in the StormPower and Control in a Union/Management Training Program - Ramo J. Lord (Adult Education Research Conference, 2015)
This study investigated how a workplace educator was used as a pawn between the company and the union while delivering a safety-training program. Among the findings were training was held in contempt by union and management while safety’s exchange value was exploited.
Keywords: workplace educator; working class; cultural historical activity theory; power; worker struggle